2014
DOI: 10.1017/s2045796014000675
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in method-specific suicide rates in Japan, 1990–2011

Abstract: Our findings revealed that different suicide methods varied in their contribution to the recent overall suicide transition in Japan. Regarding factors associated with the recent increase in suicides by overdose, gases, hanging and jumping, further research is needed in order to promote and implement effective means restriction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
6
27
0
1
Order By: Relevance
“…Thus, we reported that the most frequent method of suicide was hanging, which is followed by self-poisoning. These results are also in agreement with international evidence, which, in general, describe a superiority of suicide by hanging [43][44][45] .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we reported that the most frequent method of suicide was hanging, which is followed by self-poisoning. These results are also in agreement with international evidence, which, in general, describe a superiority of suicide by hanging [43][44][45] .…”
Section: Discussionsupporting
confidence: 92%
“…A study in Japan suggested that an increase in overdose suicide in younger generations after 2000 was the result of suboptimal prescription of psychotropic drugs [ 30 ]. Non-psychiatrists, who make up the majority of physicians in Japan, generally have less knowledge of psychotropic drugs than psychiatrists, but often prescribe them.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed data for persons aged ≥15 years because suicide is uncommon in children and early adolescence and determining suicidal intent in younger children can be difficult 19. According to previous studies,20 21 age was divided into four groups: 15–24 years, 25–44 years, 45–64 years and 65 years and older. Following preliminary analyses, we decided to combine adolescents and young adults into one age group (15–44 years) because they showed very similar suicide method patterns and changing trends in most countries.…”
Section: Methodsmentioning
confidence: 99%